The geographical distribution of poultry meat production in Iraq and the possibilities of achieving self-sufficiency - Kadhim, Zainab Kamel (Al-Adab Journal, 2021)
This study deals with the reality of poultry meat production in Iraq and the extent of development that this type of production has witnessed between 2009 and 2019, and a picture of the geographical distribution of the number of projects and the amount of their production in the country, and determining the self-sufficiency ratio for each of the governorates of Iraq, which was taken as a standard in which the amount of the achieved From consumption and to indicate the amount of deficit at the level of administrative units based on the analytical method of the data, and the future expectations of poultry meat production were extracted using the forecast function (Forecast function) so that Iraq would achieve self-sufficiency in the production of poultry meat in the long term and the lack of food gap.